A systems theory of development through sport for traumatized and disadvantaged youth. (September 2018) - Whitley, Meredith A.; Massey, William V.; Wilkison, Megan
Abstract: Objectives: The current study builds on an ongoing line of research in which the overarching purpose is to develop a theory for positive youth development through sport that examines: (a) the various roles sport can play in the development of individuals who have experienced complex and developmental trauma and were raised in under-resourced communities, and (b) how interrelated systems interact to augment a positive sport experience and engender positive developmental outcomes. Method: Utilizing both grounded theory methodology and narrative inquiry, interviews were conducted with 14 participants with extensive experience working with this population (e.g., high school counselor, physical education teacher, psychologist, coach, program manager, police officer), as well as knowledge or expertise in using sport with this population. Data collection and data analysis took place concurrently. Results and discussion: Findings were originally presented in the form of participant systems maps, which were ultimately combined for a comprehensive systems map, representing the optimal system through which youth may engage in sport. The core variables and interactions of this optimal system are presented in this manuscript. Key findings include the role of vigorous physical activity and healthy competition in youth development, the need for talent development and youth development to be complementary goals, and the potential for multiple identity development to be a critical first step in the transference of life skills into other domains. Highlights: Vigorous physical activity and healthy competition are central to youth development. Talent development and youth development should be complementary goals. Multiple identity development may need to occur before life skills can be transferred from sport to life.